Novel polymorphisms in plasmodium falciparum ABC transporter genes are associated with major ACT antimalarial drug resistance - Veiga, Maria Isabel (2018)
Chemotherapy is a critical component of malaria control. However, the most deadly malaria pathogen, Plasmodium falciparum, has repeatedly mounted resistance against a series of antimalarial drugs used in the last decades. Southeast Asia is an epicenter of emerging antimalarial drug resistance, including recent resistance to the artemisinins, the core component of all recommended antimalarial combination therapies. Alterations in the parasitic membrane proteins Pgh-1, PfCRT and PfMRP1 are believed to be major contributors to resistance through decreasing intracellular drug accumulation. The pfcrt, pfmdr1 and pfmrp1 genes were sequenced from a set of P. falciparum field isolates from the Thai-Myanmar border. In vitro drug susceptibility to artemisinin, dihydroartemisinin, mefloquine and lumefantrine were assessed. Positive correlations were seen between the in vitro susceptibility responses to artemisinin and dihydroartemisinin and the responses to the arylamino-alcohol quinolines lumefantrine and mefloquine. The previously unstudied pfmdr1 F1226Y and pfmrp1 F1390I SNPs were associated significantly with artemisinin, mefloquine and lumefantrine in vitro susceptibility. A variation in pfmdr1 gene copy number was also associated with parasite drug susceptibility of artemisinin, mefloquine and lumefantrine. Our work unveils new candidate markers of P. falciparum multidrug resistance in vitro, while contributing to the understanding of subjacent genetic complexity, essential for future evidence-based drug policy decisions.